Albumseite 43
Wirtschaft;Wirtschaftsleben;Wirtschaftsstruktur;Wirtschaftsform;Hauswirtschaft Verkehr;Landverkehr;Schienenverkehr;Bahnhof politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung